Remote forms of support for adults with intellectual disabilities during the Covid-19 pandemic in the opinions of parents and caregivers - Kamecka-Antczak, Celina; Wos-Rutkowska, Klaudia; Szafrański, Mateusz (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
Te educational and therapeutic reality for people with intellectual disabilities changed dramaticallyduring the Covid-19 pandemic. Most institutions supporting people with intellectual disabilitiesswitched to a remote mode of operation, which required adaptation to the new realitiesby people with disabilities, their immediate families, as well as therapists and institution staf. Teaim of the research discussed in this article was to fnd out the opinions of parents of adults withintellectual disabilities on the quality of remote therapy and rehabilitation ofered by day care centresduring the frst stage of the pandemic in Poland and to look for solutions to improve this processin the future. Te results of the research indicate difculties in combining professional, homeand therapeutic duties by parents of adults with intellectual disabilities, problems concerning theimplementation and conduct of therapy, lack of access to professional rehabilitation equipment orlow level of skills in using computer equipment. Concern about the regression of the child’s skillsand limited access to contact with friends was also a frequently mentioned problem. Parents’ demandsincluded: regularity of therapy, constant contact with the therapist, adjusting the scheduleto the rhythm of the day, training in the use of computer equipment, ensuring contact with peersor introducing a hybrid model – remote classes and meetings in real life. Te research conductedwas the frst in Poland to report on a qualitative evaluation of remote therapy for people withintellectual disabilities during the Covid-19 epidemic. Further, broader research is needed to fndsolutions that respect the rights of people with disabilities to education and therapy.